The Effect of Eco enzyme Application method on the Growth of Mustard Plants (Brassica juncea L.) - Riska Riska; Azwir Anhar (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Mustard (Brassica juncea L.) is a type of leaf vegetable that is favored by the public because it contains minerals, vitamins, protein, fat, carbohydrates, Ca, P, Fe, Vitamins A, B, and C. Organic fertilizers can be obtained by processing organic waste into ecoenzymes. There are different ways of applying fertilizer to plants. The purpose of study was to determine the effect of the administration of ecoenzymes on the growth of mustard greens (Brassica juncea L.). This study is an experimental using a Completely Randomized Design (CRD) consisting of 4 treatments and 6 replications. The treatments given were soaked seeds, soaked roots, watered to the ground, sprayed leaves. The data obtained were analyzed by means of variance (ANOVA) with Duncan's New Multiple Range Test (DNMRT) further test. The results showed that the method of administering ecoenzymes significantly affected plant height, leaf area, wet weight and dry weight growth of mustard greens (Brassica juncea L.). The method of administering ecoenzymes with soaked seeds gave the best results for the height, wet weight and dry weight of the mustard plant, namely with a height of 17,58 cm, leaf area of 24,34 cm2, wet weight of 5.1 g and dry weight of 0.77 g.